Cetacean stranding and diet analyses in the North Aegean Sea (Greece). (3rd April 2017) - Milani, C.B.; Vella, A.; Vidoris, P.; Christidis, A.; Koutrakis, E.; Frantzis, A.; Miliou, A.; Kallianiotis, A.
Abstract : Cetacean stranding reports in the North Aegean Sea were recorded since 1998 from Strimonikos Gulf in Chalkidiki up to Alexandroupoli on the Turkish border and in a few northern Aegean islands. On site, the specimens were examined to identify species, gender, approximate age and, when possible, cause for stranding. A total of 26 filled stomachs of five cetacean species collected since 2002 were analysed: bottlenose dolphins Tursiops truncatus (N = 8), common dolphins Delphinus delphis (N = 8), harbour porpoises Phocoena phocoena (N = 5), striped dolphins Stenella coeruleoalba (N = 4) and Risso's dolphins Grampus griseus (N = 1). From the analysed stomachs it was found that the bottlenose dolphins fed mainly on snake blenny Ophidion barbatum (34%), bogue Boops boops (22%) and round sardinella Sardinella aurita (13%); common dolphins on round sardinella (17%), picarels Spicara spp. (10%) and Cocco's lantern fish Lobianchia gemellaris (9%); harbour porpoises on Gobidae (four-spotted goby Deltentosteus quadrimaculatus 41% and black goby Gobius niger 37%) and round sardinella (7%); striped dolphins on Myctophydae (Madeira lantern fish Ceratoscopelus maderensis 51%), and on Pfeffer's enople squid Abraliopsis morisii (10%) and bogue (8%); and Risso's dolphin exclusively on Teuthidae (31%), the umbrella squid Histioteuthis bonellii (30%) and the reverse jewel squid H. reversa (14%). The present work represents the first attempt to investigate the diet up to species level for several cetaceans in Greek waters and for harbour porpoises stranded in the Mediterranean Sea.